In vitro, in vivo and clinical studies comparing the efficacy of ceftazidime-avibactam monotherapy with ceftazidime-avibactam-containing combination regimens against carbapenem-resistant Enterobacterales and multidrug-resistant Pseudomonas aeruginosa isolates or infections: a scoping review - Aslan, Abdullah Tarık; Ezure, Yukiko; Horcajada, Juan Pablo; Harris, Patrick N. A.; Paterson, David L. (Frontiers in Medicine, 2023)
Introduction Carbapenem-resistant Enterobacterales (CRE) and multidrug-resistant Pseudomonas aeruginosa (MDR-PA) infections are associated with a high risk of morbidity, mortality, and treatment costs. We aimed to evaluate in vitro, in vivo and clinical studies comparing the efficacy of ceftazidime-avibactam (CZA) combination regimens with CZA alone against CRE and/or MDR-PA isolates or infections. Methods We systematically reviewed the relevant literature in CINAHL/MEDLINE, Pubmed, Cochrane, Web of Science, Embase, and Scopus until December 1, 2022. Review articles, grey literature, abstracts, comments, editorials, non-peer reviewed articles, non-English articles, and in vitro synergy studies conducted on single isolates were excluded. Results 22 in vitro, 7 in vivo and 20 clinical studies were evaluated. In vitro studies showed reliable synergy between CZA and aztreonam against metallo-β-lactamase (MBL)-producing isolates. Some studies indicated good in vitro synergy between CZA and amikacin, meropenem, fosfomycin and polymyxins against CRE isolates. For MDR-PA isolates, there are comparatively fewer in vitro or in vivo studies. In observational clinical studies, mortality, clinical cure, adverse events, and development of CZA resistance after exposure were generally similar in monotherapy and combination therapy groups. However, antibiotic-related nephrotoxicity and infection relapses were higher in patients receiving CZA combination therapies. Discussion The benefit, if any, of CZA combination regimens in MDR-PA infections is elusive, as very few clinical studies have included these infections. There is no currently documented clinical benefit for the use of CZA combination regimens rather than CZA monotherapy. CZA combined with aztreonam for serious infections due to MBL producers should be evaluated by randomized controlled trials. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=278552, CRD42021278552.